Deauthorization of Illegal Officiants in Siri Marriages in Mallusetasi District, Barru Regency - Abdul Rahman Awan; Sudirman; Zainal Said; Fikri; M. Ali Rusdi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
This research discusses the Illegal Officiating in Siri Marriages in Mallusetasi District, Barru Regency, that siri marriages are marriages that are not registered with the Office of Religious Affairs (KUA) and are not in accordance with State laws and regulations. This type of research is field research which is carried out in the middle of the research object in order to find out and obtain clear data using qualitative description methods. Research carried out in the field examines problems of a qualitative nature. The data collected is generally in the form of words, pictures and number books. The data collection uses observation, interview and documentation techniques, by analyzing the data using data reduction, data presentation and drawing conclusions. The process of solving the main problem is of course in accordance with the main problem of formulating. The results of this research are. 1) The Social Context of Siri Marriage in Mallusetasi District, Barru Regency, the most important thing is the validity of the marriage according to religious (Islamic) law, even though legally in the country the marriage does not have legal legality. 2) The implementation procedure for a Siri Marriage in Mallusetasi District, Barru Regency is not much different from an official marriage. Siri marriages carried out in the village are legal if the harmony is fulfilled and the marriage is carried out by a local religious shop or Imam who is considered by the community to understand Islam. 3) Illegal Penghulu Authority in Siri Marriages in Mallusetasi District, Barru Regency. In fact, the celebrant does not have any authority but only helps the community to carry out their wedding. Even the informant himself still advised the public to take matters into their own hands with the KUA